Impact of COVID-19 on selected essential public health services - lessons learned from a retrospective record review in the Free State, South Africa - Christo Heunis; Perpetual Chikobvu; Michel Muteba; Gladys Kigozi-Male; Michelle Engelbrecht; Providence Mushori (BMC, 2023)
Abstract Background In an attempt to discern lessons to improve future pandemic responses, this study measured the effects of the COVID-19 pandemic on essential public health services (EPHSs) related to primary health care (PHC) and outpatient department (OPD) utilisation, antiretroviral treatment (ART) commencement, drug-susceptible tuberculosis (DS-TB) confirmation and treatment commencement, and Bacillus Calmette-Guérin (BCG) coverage, in the Free State province of South Africa during January 2019 to March 2021. Methods A pre-post study design comparing EPHS performance between 2019 and 2020/21 was employed. Routinely collected data were analysed. An interrupted time series analysis was used to measure changes in service use and outcomes from January 2019 to March 2021. Median changes were compared using Wilcoxon rank-sum tests. A 5% statistical significance level was considered. Results Over the study period, the median values for the annual number of PHC visits was 1.80, 55.30% for non-referred OPD visits, 69.40% for ART commencement, 95.10% and 18.70% for DS-TB confirmation and treatment commencement respectively, and 93.70% for BCG coverage. While BCG coverage increased by 5.85% (p = 0.010), significant declines were observed in PHC utilisation (10.53%; p = 0.001), non-referred OPD visits (12.05%; p < 0.001), and ART commencement (9.53%; p = 0.017) rates. Given the importance of PHC in addressing a new pandemic, along with the existing HIV and TB epidemics - as well as the entire quadruple burden of disease - in South Africa, the finding that the PHC utilisation rate statistically significantly decreased in the Free State post-COVID-19 commencement is particularly concerning. Conclusions The lessons learned from this retrospective review attest to a measure of resilience in EPHS delivery in the Free State in as far as a significant hike in BCG vaccination over the study period, 2019-2020/21 was observed. As evidenced by a decline in PHC service utilisation and the decreased numbers of new patients commencing ART, we also learned that EPHS delivery in the province was fragile.